Secreting-lux/pT-ClyA engineered bacteria suppresses tumor growth via interleukin-1β in two pathways - Yuqin Wu; Zhicai Feng; Shengnan Jiang; Jing Chen; Yuefu Zhan; Jianqiang Chen (AMB Express, 2019)
Abstract Engineered Salmonella typhimurium (S.t-ΔpGlux/pT-ClyA) and attenuated Salmonella typhimurium (SL: Salmonella typhimurium with a defect in the synthesis of guanine 5′-diphosphate-3′-diphosphate) exhibit similar tumor targeting capabilities (Kim et al. in Theranostics 5:1328–1342, 2015; Jiang et al. in Mol Ther 18:635–642, 2013), but S.t-ΔpGlux/pT-ClyA exerts superior tumor suppressive effects. The aim of this study was to investigate whether S.t-ΔpGlux/pT-ClyA inhibits colon cancer growth and recurrence by promoting increased IL-1β production. The CT26 tumor mouse model was used, and mice were treated in the following ways: PBS, S.t-ΔpGlux/pT-ClyA(+) + IL-1βAb, SL, S.t-ΔpGlux/pT-ClyA(−), and S.t-ΔpGlux/pT-ClyA(+). Dynamic evaluation of the efficacy of S.t-ΔpGlux/pT-ClyA in the treatment of colon cancer was assessed by MRI. Western blot, immunofluorescence and flow cytometry analysis were used to investigate IL-1β-derived cells and IL-1β expression on tumor cells and immune cells to analyze the regulatory mechanism. IL-1β levels in tumors colonized by S.t-ΔpGlux/pT-ClyA were significantly increased and maintained at high levels compared to control treatments. This increase caused tumors to subside without recurrence. We examined the immune cells mediating S.t-ΔpGlux/pT-ClyA-induced tumor suppression and examined the major cell types producing IL-1β. We found that macrophages and dendritic cells were the primary IL-1β producers. Inhibition of IL-1β in mice treated with S.t-ΔpGlux/pT-ClyA using an IL-1β antibody caused tumor growth to resume. This suggests that IL-1β plays an important role in the treatment of cancer by S.t-ΔpGlux/pT-ClyA. We found that in St-ΔpGlux/pT-ClyA-treated tumors, expression of molecules involved in signaling pathways, such as NLRP3, ASC, Caspase1, TLR4, MyD88, NF-kB and IL-1β, were upregulated, while in ΔppGpp S. typhimurium treated animals, TLR4, MyD88, NF-kB and IL-1β were upregulated with NLRP3, ASC, and Caspase1 being rarely expressed or not expressed at all. Using S.t-ΔpGlux/pT-ClyA may simultaneously activate TLR4 and NLRP3 signaling pathways, which increase IL-1β expression and enhance inhibition of colon cancer growth without tumor recurrence. This study provides a novel platform for treating colon cancer.